2017
DOI: 10.2147/ijn.s132472
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotection against apoptosis of SK-N-MC cells using RMP-7- and lactoferrin-grafted liposomes carrying quercetin

Abstract: A drug delivery system of quercetin (QU)-encapsulated liposomes (LS) grafted with RMP-7, a bradykinin analog, and lactoferrin (Lf) was developed to permeate the blood–brain barrier (BBB) and rescue degenerated neurons, acting as an Alzheimer’s disease (AD) pharmacotherapy. This colloidal formulation of QU-encapsulated LS grafted with RMP-7 and Lf (RMP-7-Lf-QU-LS) was used to traverse human brain microvascular endothelial cells (HBMECs) regulated by human astrocytes (HAs) and to treat SK-N-MC cells after an ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(31 citation statements)
references
References 43 publications
2
29
0
Order By: Relevance
“…Liposomes can also improve the water solubility, reduce the toxic effects of, and control the release of substances entrapped in them. The liposomes protect the encapsulated compound from external stimuli, such as light, enzymes, extreme temperatures, and pH variations [ 27 , 28 ]. Polymeric micelles have also been found to be very useful for encapsulating many drugs, including quercetin [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Liposomes can also improve the water solubility, reduce the toxic effects of, and control the release of substances entrapped in them. The liposomes protect the encapsulated compound from external stimuli, such as light, enzymes, extreme temperatures, and pH variations [ 27 , 28 ]. Polymeric micelles have also been found to be very useful for encapsulating many drugs, including quercetin [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Both of these studies were conducted in human neuroblastoma SK-N-MC cells, as reported by the authors. Although the SK-N-MC cell line is often used as a model for testing neuroprotective effects [58][59][60][61], it must be noted that this cell line is now widely regarded as having originated from Askin's tumor related to Ewing's sarcoma and not neuroblastoma as originally described [62].…”
Section: Urolithin Activity In the Modulation Of Oxidative Stressmentioning
confidence: 99%
“…It has been reported to be strong antioxidant because of its ability to scavenge free radicals and strong anti-inflammatory due to its inhibition of the proinflammatory cytokine TNF- α [ 2 , 3 ]. Apart from these pharmacological activities, QUT has also shown strong antiproliferative, antiviral, and neuroprotection activities [ 1 , 4 ]. In spite of these beneficial pharmacological properties, QUT's application in vivo is hampered by its low aqueous solubility and poor stability.…”
Section: Introductionmentioning
confidence: 99%